Evaluation of dentistry academic performance in higher education under active methodology: perceptions and experiences (Research, Society and Development, 2021)
The ability to acquire knowledge and skills in the academic environment is multifactorial, ranging from the quality of teaching to the commitment of the academic among other indicators, such as social, family, institutional and pedagogical aspects, which directly impact the performance of this student in evaluations. Knowing this, the evaluation of academic performance (ADA) is necessary to understand if there was a sedimentation of learning and the perception of which evaluation process develops the best performance for students and how they deal with this moment. Therefore, this research aimed to point out the perceptions and experiences of academics of higher education in evaluation under active methodology and their performance. It was a cross-sectional and retrospective study, with a qualitative approach developed through an electronic form, with 71 students from the dentistry course of a Higher Education Institution, through questions that addressed the symptoms / sensations before, during and after the evaluation, and allowed them to write reports of the important points of the experience. When analyzing the symptoms / sensations reported before, during and after the application of the active methodology, a predominance of feelings of fear and palpitation was noticed before the evaluation and, relaxation and relief after. As for the precipitating factors of symptoms / sensations that interfered in the students' performance in the evaluation under active methodology, the classroom approach of the professor of the discipline, as well as the reports of students who had already gone through the experience, stimulated the development of anxiety and stress. The previous preparation and the evaluation format stimulated tranquility and confidence. It is concluded that the evaluation of academics under active methodology can bring positive and conflicting experiences to this, however, the way the student sees the process directly interferes in their performance.